Factors of behavioural problems and types of housing of persons with intellectual disability - Tamaš Daniela; Glumbić Nenad (Specijalna Edukacija i Rehabilitacija, 2015)
Behavioural problems of adults with intellectual disability, (ID) like aggression, auto aggression and destructive behaviour, can often be caused by external factors, such as: frustration, ignoring their needs, limited choice of activities or inadequate communication. The aim of this research was to confirm the impact of different causes of behavioral problems of adults with ID depending on the type of housing. The research starts from the presumption that the intensity and appearance of behavioural problems of people with ID depend on the type of housing. The research sample consists of 122 adults with moderate ID, between 17 and 79 years of age (AS=39.95; SD=13.90). The sample is divided into three sub-samples: the first sub-sample are people with ID who live in inpatient institutions (n=51), the second sub-sample are adults with ID who live with their families (n=38) and the third sub-sample are people with ID who are included in the programme of supported housing (n=33). The questionnaire 'Questions About Behaviour Functions' (QABF, Matson & Vollmer, 1995) was used in this research. The research results show that the type of housing of adults with ID influences the presence of behavioural problems. Statistically significant differences were present in all variables which indicate different causes of behavioural problems with regard to the type of housing. In the subsample of the examinees included in the programme of supported housing, behavioural problems are statistically less present comparing to the other two subsamples(p=0.000). The participants who live in families and institutions have similar results, except in the variable of material cause of problematic behaviour, where statistically significant differences were present in all three sub-samples. The age of participants does not have statistically significant effect on the appearance of behavioural problems factors.